COMPUTER-AID DRAWING AND DESIGN - Faxriddinov Muhammad Faxriddin o‘g‘li (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article will talk about the role of modern technologies in education in the present day. In the current rapidly developing world, the role of the” IT " sphere is clearly distinguished. With such an origin, the use of a computer and the design of drawings on it also occupy a special place in the disciplines of drawing. The article covered.